2017
DOI: 10.3892/or.2017.6072
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 overexpression occurs in various important cancer types and is linked to aggressive tumor features: A tissue microarray study on 8,877 human cancers and normal tissues

Abstract: IMP3 is an RNA binding protein required for ribosomal RNA processing, which has been suggested to be a prognostic marker in a large variety of human types of cancer. However, available data on the prevalence of IMP3 expression are largely discrepant. To systematically investigate the epidemiology and clinical relevance of IMP3 expression in human cancers we employed a two-step tissue microarrays (TMAs) approach. First, a normal tissue TMA and a multi-tumor TMA were analyzed for immunohistochemically detectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 91 publications
3
71
0
Order By: Relevance
“…The siRNA effect will diminish after a few days so that we believe that the reduced tumor size was due to a transient inhibition, which amounted to a delayed start in tumor growth. Further, we reported another mechanism by which IGF2BP3 knockdown reduced the MMP2 and MMP9 protein levels in OCCC, as shown in triple negative breast cancer before (20). Because IGF2BP3 is able to bind multiple target RNAs, thereby altering their stability, translatability and/or localization, we predict that it may function directly or indirectly to modify the expression of the various gene products, including MMPs, PCNA or other proteins involved in the control of cell proliferation, death, migration and invasion as shown in this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The siRNA effect will diminish after a few days so that we believe that the reduced tumor size was due to a transient inhibition, which amounted to a delayed start in tumor growth. Further, we reported another mechanism by which IGF2BP3 knockdown reduced the MMP2 and MMP9 protein levels in OCCC, as shown in triple negative breast cancer before (20). Because IGF2BP3 is able to bind multiple target RNAs, thereby altering their stability, translatability and/or localization, we predict that it may function directly or indirectly to modify the expression of the various gene products, including MMPs, PCNA or other proteins involved in the control of cell proliferation, death, migration and invasion as shown in this study.…”
Section: Discussionmentioning
confidence: 63%
“…IGF2BP3 has been reported to be involved in the progression of various cancers, including those in the pancreas (11), colon or rectum (17), lungs (18), and ovaries (19). According to a study with microarray assays of 8,877 human cancers and normal tissues, IGF2BP3 is associated with aggressive tumor features and unfavorable outcomes (20). In lung adenocarcinoma, overexpression of IGF2BP3 may induce the proliferation of cancer cells by mRNA degradation (21).…”
Section: Introductionmentioning
confidence: 99%
“…The upregulated RBPs were remarkably enriched in ncRNA processing, tRNA metabolic process, cytoplasmic ribonucleoprotein granule, RNA transport, spliceosome, and mRNA surveillance pathway. Burdelski et al had previously reported the role of RNA processing in various cancer types [36]. In some cases, tumors utilize the mRNA surveillance pathway to downregulate gene expression by destroying key tumor-suppressor mRNAs, whereas in other cases, tumors adapt to their microenvironment by regulating the activity of mRNA surveillance pathway [37].…”
Section: Discussionmentioning
confidence: 99%
“…IMP3 (Insulin‐like growth factor mRNA‐binding protein 3) is a member of the IMP family and has shown to be expressed at low or undetectable protein levels in normal adult tissues . In contrast, in several malignant tumors IMP3 protein expression is strongly up‐regulated . Furthermore, IMP3 protein expression has been identified as an independent prognostic factor in a series of tumors such as oral, breast, colorectal and bladder cancer .…”
Section: Introductionmentioning
confidence: 99%